Evaluating the Effectiveness of an Online Intervention to Educate College Students About Dating Violence and Bystander Responses - O’Brien, Karen M. (Journal of interpersonal violence, 2021)
The purpose of this study was to conduct a randomized controlled trial to assess the efficacy of STOP Dating Violence, an online intervention developed to educate students about dating violence and appropriate bystander interventions on college campuses. College students (N = 317) were randomly assigned to one of the three conditions: (a) the STOP Dating Violence intervention, (b) a website containing information about dating violence, or (c) a control condition. Participants completed pre- and posttest quantitative and qualitative measures to assess knowledge of warning signs and appropriate bystander behaviors, attitudes about intervening as a bystander, willingness to intervene, and self-efficacy regarding intervening. The results indicated that students who participated in the STOP Dating Violence intervention were the most knowledgeable about jealous warning signs of dating violence and appropriate bystander interventions, had the greatest intent to assist a victim of dating violence, and were the most confident in their ability to intervene in dating violence situations, when compared with participants in the website and control conditions. Those who participated in the intervention also demonstrated greater knowledge regarding appropriate bystander behaviors 1 month following the intervention. No differences were found in attitudes regarding helping someone in an abusive dating relationship or engagement in bystander behaviors at follow-up. Qualitative analyses provided further support for the efficacy of STOP Dating Violence in increasing knowledge of barriers to bystander intervention and appropriate bystander intervention strategies in dating violence situations. Overall, the STOP Dating Violence intervention has the potential to educate undergraduates about dating violence and bystander interventions on college campuses.